DEVELOPMENT OF CONCEPT OF EQUVALENCE IN CONTRACT LAW THROUGH RULES ON FAIR PRICE FROM ANCIENT TIMES TO EARLZ 20TH CENTURY - Martinov, Darija (Glasnik Advokatske komore Vojvodine, 2023)
The origin of the principle of equivalence in contract law, as well as its subsequent development, is closely related to the rules on fair price. By showing the evolution of the concept of fair price from ancient times, through the rules of Roman law, medieval anc canon law concepts to the first codes of law in the 19th and 20th centuries, in this paper we will show the gradual change in understanding of what a fair price denotes, under what conditions it ought to be applied, whether it should be legislatively regulated and to what extent, as well as in what way this legal institute depicts and protects the equality/fairness of mutual considerations in contract law. In doing so, we will keep in mind the intertwining of this institute with the institute of laesio enormis (excessive damage), whose evolution has also had an impact on the formation of the concept of fair price as we know it today.